The Role of Entrepreneurship Education in Enhancing Students' Innovation Capability and Competitiveness in Facing the 4.0 Era - Nining Wahyuningsih; Rudi Salam; Mila Kurnia Pinandita; Rina Setyaningsih (International Journal Labs, 2025)
Economic globalization has brought significant changes to the labor market structure, where competition is no longer limited to the local or national level but extends across international borders. In this context, university graduates are required not only to possess academic knowledge but also innovative capabilities and entrepreneurial skills to compete globally. Data from the Central Statistics Agency (BPS) in 2024 shows that 11.28% of bachelor’s, master’s, and doctoral graduates between August 2022 and August 2024 were unemployed, highlighting the urgency of strengthening entrepreneurship education. This research aims to analyze The Role of Entrepreneurship Education in Enhancing Students' Innovation Capability and Competitiveness in Facing the 4.0 Era. A qualitative method, through a literature review, was employed, analyzing various relevant sources such as journals, books, and articles published in the last five years. The results indicate that entrepreneurship education plays a crucial role in shaping an innovative mindset, building self-confidence, and preparing students to create their own job opportunities. Effective implementation requires competent lecturers, adequate infrastructure, and sustainable programs integrated with technological developments. Thus, entrepreneurship education not only enhances individual competencies but also contributes to reducing unemployment rates and supporting national economic growth.